The role of the midwife as an implementer in handling risk 4T in Puskesmas Basah Rice, Pangkalan Susu subdistrict, Langkat district in 2021 - Siti Nurmawan Sinaga (Institute of Computer Science (IOCS), 2022)
A midwife is a woman who has attended and completed midwifery education that has been recognized by the government and passed the examination with applicable requirements and has qualifications to obtain a license to practice midwifery. Midwives have a very important role in reducing maternal mortality (MMR), the MMR in Indonesia is 307/100,000 births. The purpose of this study was to find out how the role of midwives as implementers in dealing with the 4 T risks at the Beras Basah Health Center, P. Susu District, Langkat Regency in 2021. This research was conducted using a descriptive method with a sample of 32 people. The sampling method was all midwives on duty at the Beras Basah Health Center, P.Susu District, Langkat Regency in 2021. By using the total sampling method. This research was conducted in June 2021. As a result of the study, it was found that the role of the midwife as implementer in dealing with 4T risks at the Beras Basah Health Center P. Susu Subdistrict, Langkat Regency in 2021. Based on the age most found at the age of 34-35 years as many as 13 people (40.6%), the most educated had D3 education, namely 23 people (71.9%), the longest working period a lot of work experience that is >10 years as many as 16 people (50.0%), then the role that midwives have in a good category is as many as 32 people (100%). It was concluded that the role of midwives as implementers in handling the 4 T risk at the Beras Basah Health Center, P. Susu District, Langkat Regency in 2021, had a good role.